Optimal monetary policy in a small open economy with financial frictions - Rossana Merola (Deutsche Bundesbank, 2010)
I analyze how the introduction of financial frictions can affect the trade-off between output stabilization and inflation stability and whether, in the presence of financial frictions, the optimal outcome can be realized or approached more closely if monetary policy is allowed to react to aggregate financial variables. Moreover, I explore the issue of whether an inflation targeting cum exchange rate stabilization and a price-level targeting are more suitable rules in minimizing distortions generated by the presence of liabilities defined in foreign currency and in nominal terms. I find that, when the financial accelerator mechanism is working, a price-level targeting rule dominates. One caveat is that the source of the shock plays an important role. Once the financial shock is not operative, the gain from a price-level targeting rule decreases significantly.
Keywords: E31; E44; E52; E58; 330; Monetary policy; Taylor rule; financial accelerator; price-level targeting; asset prices; Geldpolitik; Reaktionsfunktion; Taylor-Regel; Finanzmarkt; Unvollkommener Markt; Kleines-offenes-Land; Wechselkurspolitik; Theorie